Studies toward the total synthesis of mulberry dielsalder adducts morusalbanol A and sorocein B / Tee Jia Ti - Tee, Jia Ti (2016)

(untitled)
Morusalbanol A (42) and sorocein B (62) are biologically active natural products isolated from moraceous plants. They are postulated to be biosynthetically derived from an intramolecular cyclization/ketalization of a cis-trans mulberry Diels-Alder adduct. Thus far, there has been no report on the synthesis of these compounds since their first isolation in 1991. A model studies on construction of the oxabicyclic [3.3.1] core of morusalbanol A was conducted prior to embarking on the synthesis of morusalbanol A and sorocein B. The results showed that the required cis-trans Diels-Alder precursors of morusalbanol A was obtained via the thermal cycloaddition reaction which was proven to be dependent on the presence of a hydrogen-bonded ortho OH substituent on the chalcones dienophile. Acid catalyzed intramolecular cyclization of a cis-trans Diels-Alder adduct (endo-181) afforded the desired oxabicyclic [3.3.1] core of morusalbanol A in a stereocontrolled manner. Results from the model study have been applied to the synthesis of morusalbanol A (42). The requisite cis-trans Diels-Alder precursor (endo-204) of morusalbanol A was successfully prepared via the thermal cycloaddition reaction between the methyl ether protected chalcones dienophile 88 and the dehydroprenyl diene 191. Selective removal of the ortho OMe group of the endo-204 by using MgI2 gave (±) morusalbanol A methyl ethers 206 and 207. A number of key proton and carbon signals in the NMR spectra of 206 and 207 were absent as a result of atroisomerism due to the rotational hindrance of the Diels-Alder-rings about the C5´´-15´´ and C4´´-C8´´-C9´´ bond. Global demethylation on the (±) morusalbanol A methyl ethers 206 and 207 by using MgI2, BCl3, TMSI-quinoline was unsuccessful. An efficient method for preparing 2´2-dimethyl-2H-chromones via Pd(II)-catalyzed Heck coupling of o-halophenols with 2-methyl-3-buten-2-ol has been developed during the synthesis of sorocein B. The method is very general and can be useful to the synthesis of some natural 2´,2-dimethyl-2H-chromones. Similar strategy was used for construction of the cis-trans Diels-Alder precursor of sorocein B. The thermal cycloaddition reaction between chalcones dienophile 89 and dehydroprenyl diene 106 afforded the requisite cis-trans Diels-Alder precursor (endo-241) in 35% yield along with the trans-trans Diels-Alder diastereomer. Subsequently PdCl2 catalyzed cyclization of the ortho-prenyl group of endo-241 afforded the required 2,2-dimethylchromenyl ring in 230. However, attempts to remove the methyl ether group of 230 to form sorocein B with BCl3, MgI2, and TMSI-quinoline were unsuccessful.